A APAC (ASSOCIAÇÃO DE PROTEÇÃO E ASSISTÊNCIA AO CONDENADOS) E O PROCESSO DE “RESSOCIALIZAÇÃO” NO SISTEMA CARCERÁRIO EM SÃO LUÍS DO MARANHÃO - AZEVEDO, Rodrigo Martins (2023)
The present study had as its primary objective the understanding of the dynamics and configurations related to the prison institution. This investigative endeavor was conducted based on the experience of the Association for the Protection and Assistance to Convicted Persons (APAC) São Luís, taking into consideration the underlying philosophical principles of APAC and the conception of an alternative incarceration model in response to the crisis afflicting the penal system. The management model of APAC originated from voluntary Christian experiences in the 1970s, with the initial purpose of providing spiritual support to inmates at the Humaitá prison located in São Paulo. It is important to note that this model renounces the traditional concept of "resocialization," as its proponents closely observed the numerous failures of the Brazilian prison system and consequently developed the notion of "recovery" as an alternative. To underpin the analysis of the prison institution, two classical studies play a fundamental role: Erving Goffman's work "Asylums: Essays on the Social Situation of Mental Patients and Other Inmates," in which the author elaborates on the concept of the "total institution," and Michel Foucault's "Discipline and Punish: The Birth of the Prison," in which the author explores the category of the "disciplinary institution." Both works address the prison as a mechanism of control and social transformation, albeit with distinct focuses. In an attempt to examine the prison in a contextualized manner, we incorporate the institutional perspective, recognizing the existence of a complex network of interconnected functional structures in the social sphere to comprehend the social configurations at play. Due to the constraints imposed by the COVID-19 pandemic, our research objectives and strategies had to be adapted. Empirical data for the study were obtained through direct observation and documentary research. The process of institutionalizing practices and discourses legalized within APAC was examined, highlighting the updating of a regime of thought that is legitimized in our society, even though it has not resolved the inherent dilemma of the prison issue.